Cx43 Isoform GJA1-20k Promotes Microtubule Dependent Mitochondrial Transport - Fu, Ying; Zhang, Shan-Shan; Xiao, Shaohua; Basheer, Wassim A.; Baum, Rachel; Epifantseva, Irina; Hong, TingTing; Shaw, Robin M. (Frontiers in Physiology, 2017)
Connexin 43 (Cx43, encoded by GJA1) is a cell-cell communication gap junction protein expressed in all organ systems. It was recently found that GJA1 mRNA undergoes alternative translation to generate N-terminal truncated isoforms, of which GJA1-20k is the most abundant. Here we report a surprising finding that, unlike full length GJA1-43k, GJA1-20k have a strong tropism for mitochondria. Exploring function, we found that GJA1-20k appears to be an organelle chaperone and that overexpression of GJA1-20k is sufficient to rescue mitochondrial localization to the cell periphery upon exposure to hydrogen peroxide, which effectively limits the network fragmentation that occurs with oxidative stress. By high-resolution fluorescent imaging and electron microscopy, we determined that GJA1-20k is enriched at the interface between mitochondria and microtubules, appearing to load organelles for transport. Mutagenesis experiments revealed that although the microtubule-binding domain (MTBD) in GJA1-20k is not necessary for protein localization to mitochondria, the MTBD is essential for GJA1-20k to facilitate mitochondrial transport and maintain mitochondrial localization at the periphery. These results reveal an unexpected role for the alternatively translated isoform of the Cx43 gap junction protein, GJA1-20k, which is to facilitate microtubule-based mitochondrial transport and to maintain mitochondrial network integrity during cellular stress.